A DECONSTRUCTION OF CHARACTERS IN â€œSPONGEBOB MOVIE: SPONGE ON THE RUNâ€ - Eno Nur Hasanah; Norma Ita Solichah (English Language Teaching Journal, 2022)
This research discussed the deconstruction of characters, which aimed to deconstruct a binary opposition between the main character and minor character in SpongeBob Movie: Sponge on the Run. The researcher used note taking as an instrument to get the valid data. Primary data in this study was taken from the dialogue of the characters in the "SpongeBob Movie: Sponge on the Run" and watching in YouTube to get the data needed including the movie. So, secondary data in this study was taken from the movie and dialogue scripts in the movie by some of the characters in the movie. The findings showed that the main character in this movie was SpongeBob. SpongeBob is brave enough to defy a seven- seas king in order to save Gary, his pet. SpongeBob was portrayed as a brave, unique, and never-given-up to realizing his purpose. And the minor characters in this movie played an important role in the movie because they formed the basis for SpongeBobâ€™s character to be a brave boy. Keywords: Deconstruction, Character, SpongeBob Movie: Sponge on the Run